2008
DOI: 10.1523/jneurosci.0204-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Product-Dependent Activation of p38 Mitogen-Activated Protein Kinase Contributes to Amyloid-β-Mediated Cortical Synaptic Dysfunction

Abstract: Soluble amyloid-␤ (A␤) peptide is likely to play a key role during early stages of Alzheimer's disease (AD) by perturbing synaptic function and cognitive processes. Receptor for advanced glycation end products (RAGE) has been identified as a receptor involved in A␤-induced neuronal dysfunction. We investigated the role of neuronal RAGE in A␤-induced synaptic dysfunction in the entorhinal cortex, an area of the brain important in memory processes that is affected early in AD. We found that soluble oligomeric A␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
180
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(200 citation statements)
references
References 75 publications
19
180
1
Order By: Relevance
“…These observations agree with the concept that amyloid precursor proteins, not amyloid fibrils, cause organ dysfunction and contribute to the pathophysiology and progression in various amyloid-related diseases (7,8). Among the multiple key mediators involved in the regulation of redox status, stress-responsive p38 mitogen-activated protein kinases (MAPK) have been reported to be activated in other types of amyloid disease such as Alzheimer's disease (9)(10)(11)(12). Our prior findings have implicated oxidative stress in AL-LC-induced cellular dysfunction.…”
supporting
confidence: 86%
“…These observations agree with the concept that amyloid precursor proteins, not amyloid fibrils, cause organ dysfunction and contribute to the pathophysiology and progression in various amyloid-related diseases (7,8). Among the multiple key mediators involved in the regulation of redox status, stress-responsive p38 mitogen-activated protein kinases (MAPK) have been reported to be activated in other types of amyloid disease such as Alzheimer's disease (9)(10)(11)(12). Our prior findings have implicated oxidative stress in AL-LC-induced cellular dysfunction.…”
supporting
confidence: 86%
“…However, more recently, it has been appreciated that oligomeric and prefibrillar A␤ and A␤ have similar cytotoxic effects (34) and such soluble forms of A␤ are believed to play a critical role in the pathogenesis of AD. Recent work has demonstrated that oligomeric A␤ , at a concentration of 200 nM, is capable of blocking long-term potentiation at cortical synapses in the hippocampus and entorhinal cortex (10,28,35,36). Taken together, our findings suggest that via RAGE, neuronal transmembrane transport of A␤ and A␤ carries soluble assemblies of amyloid peptide into the cell.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, Arancio et al (28) reported increased phosphorylation of CREB, ERK1/2, p38 MAPK, and CaMKII in hippocampal extracts from Tg mice overexpressing RAGE and mAPP. RAGE-dependent activation of p38 signal transduction also plays an important role in A␤-mediated synaptic failure (35,36). However, direct links between RAGE-mediated signaling pathways and A␤ neurotoxicity remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given that the inhibition of p38 activation is sufficient to prevent Aβ-induced neurotoxicity, as also observed by others [33,56] , atorvastatin treatment controls AβO-induced neurotoxicity through the regulation of p38MAPK phosphorylation. Activated p38MAPK is observed in human AD brain tissue [57] and in AD-relevant animal models [58,59] , and cell culture studies strongly implicate p38MAPK in the increased production of proinflammatory cytokines in the glia activated by Aβ [60] .…”
Section: Discussionsupporting
confidence: 61%